Anomalous origin of circumflex coronary artery from right pulmonary artery in a hypoplastic left heart syndrome child - Jaworski, Radoslaw; Kansy, Andrzej; Łaniewski-Wołłk, Przemysław (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2014)
We describe the case of a newborn with hypoplastic left heart syndrome (HLHS) and aberrant origin of the circumflex coronary artery from the right pulmonary artery. The patient underwent a modified Norwood procedure with direct reimplantation of the circumflex coronary artery to the neo-aorta, but died on the 5th postoperative day because of myocardial failure. Detailed assessment of coronary arteries as part of the routine echocardiographic evaluation of HLHS and intraoperative inspection of them is crucial.